Kinetics and nadir of responses to immune checkpoint blockade by anti-PD1 in patients with classical Hodgkin lymphoma. (March 2018) - Dercle, Laurent; Ammari, Samy; Seban, Romain-David; Schwartz, Lawrence H.; Houot, Roch; Labaied, Nizar; Mokrane, Fatima-Zohra; Lazarovici, Julien; Danu, Alina; Marabelle, Aurélien; Ribrag, Vincent; Michot, Jean-Marie
Abstract: Background: We aimed to define the depth and time of maximal anti-tumour response to programmed death-1 blockade antibodies (anti-PD1) in heavily pre-treated patients with classical Hodgkin lymphoma (HL). To this end, we evaluated the kinetics of response for up to two years. Materials and methods: The 18F-FDG positron-emission tomography (PET) and contrast-enhanced computerised tomography (CECT) data of all relapsed or refractory HL treated at Gustave Roussy, Villejuif, France, from 2013 to 2015 were retrospectively reviewed according to the International Harmonisation Project Cheson 2014 criteria and the LYmphoma Response to Immunomodulatory therapy Criteria (LYRIC). Results: Sixteen patients were included. The median (range) treatment duration was 18.4 (2.8–23.7) months. Fifty-six percent of patients (9/16) achieved an objective response at 3 months, including 19% (3/16) of complete response. Seventeen percent (1/6) of partial responders at 3 months were converted in a complete response. 22% (2/9) of responders at 3 months relapsed before one year. The nadir was reached at 12.7 (3.0–23.0) months. The median (range) depth of response at nadir was −77% (−50% to 100%). Conclusion: We concluded that complete metabolic responses occurred within 6 months, a minority of partial responses were converted in complete response, and the median nadir was observed one year after treatment initiation. These data could help to better define the optimal treatment strategy by PET or CECT-directed approaches. Highlights: Anti-PD1 induced an early anti-tumour activity, as compared with the pre-treatment period in 6/6 patients. 62% (10/16) of patients experienced an objective response. 22% (2/9) of 3-month responders relapsed before one year. 17% (1/6) of 3-month partial responders were converted in a complete response. The nadir was observed 12.7 months after anti-PD1 initiation with a depth of response at −77%.